Synthesis and electrochemical performance of transition metal oxide anodes in lithium ion batteries - Teh, Pei Fen (2014)
To answer the intensive quest for enhanced lithium ion battery equipped to future automobiles and other advanced applications, new generation anode with good storage properties, great safety and low production cost is currently extensively explored. Transition metal oxides are one of the mostly studied candidates, which are able to uptake/release lithium ions through a new operating concept, ‘conversion reaction’. However, several factors currently handicap the conversion reaction-based anodes from commercialization. Hence, scientific research and breakthroughs to meet the application requirements are still an imperious need. A series of transition metal oxides crystallizing in spinel structure (AB2O4) prepared by different synthesis techniques is presented in this thesis, and their electrochemical performance as lithium ion battery anode is discussed in depth. This thesis mainly aims to access the common issues encountered in conversion reaction from three different perspectives, i.e. practicality of nanomaterials in enhancing the battery performance, comprehensive characterization of the reaction mechanism between spinel-based anodes and lithium ions, as well as the impact of counter ion substitution (either A- or B-sites in AB2O4 spinel) on the electrochemical properties. Based on the results of systematic cation substitution in spinels with different nanostructures, the battery performance of transition metal oxides is found to be highly contingent upon the morphology of host materials. The mixed transition metal oxides demonstrate the possibility to achieve better storage properties and greater energy density by selecting the best counter ion pairs. As a result, ZnMn2O4 and ZnFe2O4 anodes are observed to possess better lithium storage characteristics than other combination of mixed oxides, indicating their promising potential to replace currently used commercial graphite. To account for their excellent battery behaviors, detailed characterizations on cycled electrodes are conducted, especially on ZnFe2O4.